Unveiling the deformation mechanism of highly deformable magnesium alloy with heterogeneous grains. (December 2022) - Zhang, Zhi; Zhang, Jinghuai; Wang, Wenke; Liu, Shujuan; Sun, Bin; Xie, Jinshu; xiao, Tingxu
Abstract: Poor formability at room temperature is a key problem that limits the application of Mg alloys. Formability is closely dependent on both large work-hardening capacity and high tensile elongation. Herein, we develop a Mg-3Al-1Zn-0.4Mn (wt%) alloy with heterogeneous grains, obtaining an exceptionally high difference between ultimate tensile strength (UTS) and yield strength (YS) (UTS−YS: 164 MPa) and a good tensile elongation (22%). The uneven deformation of large and small grains is mainly affected by the size difference between grains rather than texture. The high strain hardening is attributed to the pile-up of geometrically necessary dislocations at grain boundaries between large and small grains due to uneven microstrain. The fraction of non-basal dislocations increases greatly with the increase of tensile strain, contributing to the improved ductility. Thus, we put forward a new strategy for improving the formability potential of Mg alloys via introducing heterogeneous-grained structure. Graphical abstract: Image, graphical abstract